2022
DOI: 10.1371/journal.pone.0276469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parental overweight and obesity on offspring’s mental health: A meta-analysis of observational studies

Abstract: Background Children of parents who were overweight/obese prior to pregnancy face a variety of neurodevelopmental challenges. The goal of this meta-analysis is to compile evidence about the impact of parental overweight/obesity on their children’s mental health. Methods The databases Cochrane Library, EMBASE, Pubmed, PsycINFO, and Web of Science were searched until May 2022. The pooled effect size was calculated using the fixed and random effect models. We also performed I2 index, subgroup analyses, sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…There is a growing awareness that parental obesity may lead to adverse long‐term health consequences for subsequent generations. Both epidemiological and animal studies have provided evidence suggesting that either maternal or paternal obesity independently increases the risk of obesity, metabolic disorders, and mental health impairments in offspring 3–5 . A recent meta‐analysis of observational human studies indicated that specifically paternal obesity, rather than overweight, was significantly associated with mental disorders in offspring, such as anxiety, attention‐deficit/hyperactivity disorder (ADHD), and autism spectrum disorder (ASD) 5 .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing awareness that parental obesity may lead to adverse long‐term health consequences for subsequent generations. Both epidemiological and animal studies have provided evidence suggesting that either maternal or paternal obesity independently increases the risk of obesity, metabolic disorders, and mental health impairments in offspring 3–5 . A recent meta‐analysis of observational human studies indicated that specifically paternal obesity, rather than overweight, was significantly associated with mental disorders in offspring, such as anxiety, attention‐deficit/hyperactivity disorder (ADHD), and autism spectrum disorder (ASD) 5 .…”
Section: Figurementioning
confidence: 99%
“…Both epidemiological and animal studies have provided evidence suggesting that either maternal or paternal obesity independently increases the risk of obesity, metabolic disorders, and mental health impairments in offspring. [3][4][5] A recent meta-analysis of observational human studies indicated that specifically paternal obesity, rather than overweight, was significantly associated with mental disorders in offspring, such as anxiety, attention-deficit/hyperactivity disorder (ADHD), and autism spectrum disorder (ASD). 5 However, establishing a casual link between parental obesity and neurocognitive development in offspring has been challenging in human studies, primarily due to the confounding effects of genetic factors and postnatal environment.…”
Section: E D I T O R I a L How Can Paternal Obesity Impair Memory Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to assess the impacts of maternal obesity on the etiology of ASD. A meta-analysis by Zhang and colleagues observed the impact of maternal overweight/obesity on the mental health of children [ 117 ]. They highlighted that maternal obesity before pregnancy increased the risk of ASD [OR 1.37 (95% CI 1.22, 1.55)], as well as other neurodevelopmental alterations [ 117 ].…”
Section: The Influence Of Environmental Hazardsmentioning
confidence: 99%
“…Subsequent studies have confirmed this increased risk of ADHD in the children of obese women. Paternal obesity has also been implicated with risk for offspring, but the association remains controversial [84][85][86].…”
Section: Additional Offspring Health Consequencesmentioning
confidence: 99%